Rendering in interior design education: challenges and curricular opportunities Abstract - Peixoto, Pedro Enrrique Silva; Dantas, Ney de Brito (DAT Journal, 2026)
Rendering is an essential stage in the representation of Interior Design projects, allowing the creation of photorealistic images that facilitate communication between professionals and clients. This technical skill has gained increasing prominence in the job market, becoming a growing requirement in the hiring processes of interior designers. This article investigates how Interior Design program coordinators in Brazil perceive the teaching of rendering within academic curricula. Through a qualitative and quantitative analysis of the collected responses, the study explores institutional dynamics, pedagogical priorities, and the strategies adopted to address the gaps between the education provided and market demands. The results highlight a general recognition of the importance of rendering for professional training but also reveal a significant gap between theory and practice in higher education.